You Are My Way to the Universe: Critical Collective Research Through Feminist Community Building - Pengfei Zhao; Dajanae Palmer; Samantha Silberstein; Alycia Elfreich; Suparna Bose; Sylvia Washington; Pooja Saxena; Lucinda Carspecken; Barbara Dennis (Forum: Qualitative Social Research, 2022)
In this article, we draw on the scholarship of feminist communitarianism to develop a critique of the predominant neoliberal qualitative social research collaboration model. We argue that feminist theories and praxis about community building and political activism have the potential to transcend the highly institutionalized, individualistic, and managerialist collaborative culture. Feminist insights can help today's researchers navigate collaborative research and address key issues such as reflexivity, consensus formation, knowledge validation, and group solidarity. We use our own work in the Feminist Research Collective and in the WomenWeLove project to present an alternative orientation and a collective way to enact transformative research. This feminist intervention against the neoliberal research culture contributes to the ongoing reflections of how we produce knowledge via qualitative social research and why we shall do so in the current historical juncture, expands our imaginations of researchers' responsibilities, and engenders new possibilities for resistance and emancipation.